A simplified delamination modelling methodology for triaxial braided composites with macro-scale solid finite-element models. Issue 1 (2nd January 2019) - Tan, Huancheng; Liu, Lulu; Guan, Yupu; Chen, Wei; Zhao, Zhenhua
ABSTRACT: Using solid elements in the commercial code ANSYS/LS-DYNA, a finite element model of two-dimensional triaxially braided composites(2DTriBCs) on a macro-scale is developed. This model employs a widely used unit cell-based approach, and each unit cell is divided into six subcells. To investigate the inter-delamination, a simplified surface-based cohesive model is established and a self-compiled post-progressing program is developed which can generate a series of figures indicating the evolution process of damage morphology and quantify the area of inter-delamination vividly. In order to validate this model, four types of 2DTriBCs with braiding angle 30, 45, 60, and 75 degree are modelled and sbjected to flat-nose and hemispherical-nose cylindrical projectiles with the equivalent mass, respectively. Results show that the braiding angle is a key element in the material response and 45 degree braiding angle architecture is more balanced in all directions due to quasi-isotropic property and has comparatively small inter-delamination area.